Prion-dependent proteome remodeling in response to environmental stress is modulated by prion variant and genetic background. Issue 1 (1st January 2019) - Allwein, Ben; Kelly, Christina; Kammoonah, Shaima; Mayor, Thibault; Cameron, Dale M.
ABSTRACT: A number of fungal proteins are capable of adopting multiple alternative, self-perpetuating prion conformations. These prion variants are associated with functional alterations of the prion-forming protein and thus the generation of new, heritable traits that can be detrimental or beneficial. Here we sought to determine the extent to which the previously-reported ZnCl2 -sensitivity trait of yeast harboring the [ PSI + ] prion is modulated by genetic background and prion variant, and whether this trait is accompanied by prion-dependent proteomic changes that could illuminate its physiological basis. We also examined the degree to which prion variant and genetic background influence other prion-dependent phenotypes. We found that ZnCl2 exposure not only reduces colony growth but also limits chronological lifespan of [ PSI + ] relative to [ psi − ] cells. This reduction in viability was observed for multiple prion variants in both the S288C and W303 genetic backgrounds. Quantitative proteomic analysis revealed that under exposure to ZnCl2 the expression of stress response proteins was elevated and the expression of proteins involved in energy metabolism was reduced in [ PSI + ] relative to [ psi − ] cells. These results suggest that cellular stress and slowed growth underlie the phenotypes we observed. More broadly, we found that prion variant and genetic background modulate prion-dependent changes in protein abundance and can profoundly impact viability in diverse environments. Thus, access to a constellation of prion variants combined with the accumulation of genetic variation together have the potential to substantially increase phenotypic diversity within a yeast population, and therefore to enhance its adaptation potential in changing environmental conditions.